GAYA HIDUP HIJABERS COMMUNITYKOTA PEKANBARU - Handayani, Sri; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The study is titled “Lifestyle Hijabers Community Pekanbaru city” Researchers interested in the theme of this because there are many Muslim women contemporary hijab users who join and form a community. In this community, a lot going on various phenomena which deserves to be investigated One form of such phenomena is a lifestyle that involves a series of patterns of consumption and leisure activity. That certainly raises a positive or negative effect on the appearance as well as they wear the hijab and their leisure time activities that seem high class.To find out the results of this study the authors use data collection techniques with observation and in-depth interviews with respondents. The sampling method or the respondent done with techniques snowball sampling where the determination of the informant is determined on an ongoing basis where the informant subsequently determined from the first informant and so on. Informants are 8 people from the community Hijabers, author stops on informants to 8 because the author felt quite obtain the desired data to answer all the research questions. The theory used in this study is a lifestyle, community, social groups, symbolic interactionism, and the history of the hijab. The method used is descriptive qualitative.The results of this study indicate a change in the use of the hijab that was originally simple use of the hijab and Muslim women as a symbol of devotion to religion has now become a lifestyle and fashion which can be seen from the pattern of consumption, leisure time activities and the factors that affect the lifestyle of the city pekanbaru Hijabers.The results of the study are expected capable of providing an overview to all parties who need information about Lifestyle Community Hijabers PekanbaruKeywords: Community, Hijabers, lifestyle